Thinking Inside the Box: How to Tailor Gamified Educational Systems Based on Learning Activities Types - Rodrigues, Luiz; Oliveira, Wilk; Toda, Armando M.; Palomino, Paula T.; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Selecting gamification elements suitable for specific players (personalization) has been sought to improve the impacts of Gamified Educational Systems (GES). However, the lack of context might be a factor on the inconsistent results of those approaches. To address this lack, we introduce a method for personalizing GES based on learning activities types. The assumption is that selecting gamification elements for specific types of learning activities has the potential to improve GES impact on users by considering the context of each activity and, thus, contributing to their learning process. We describe how to apply our approach, how it differs from user-based methods, as well as discuss three cases of application and challenges yet to be tackled.